Chest Pain? An Unusual Presentation of Vertebral Osteomyelitis - Cristian Landa; Stanley Giddings; Pramod Reddy (Case Reports in Medicine)
We present a case of vertebral osteomyelitis presenting as chest pain. The patient initially underwent a CT chest angiogram to rule out a pulmonary embolism, which incidentally showed a soft tissue vertebral mass at T3-T4 disk space. Subsequent thoracic vertebral MRI was consistent with osteomyelitis with cord compression. Tissue culture from a CT-guided biopsy grew MRSA. The patient was successfully treated with Vancomycin. This is a rare presentation of vertebral osteomyelitis which poses an interesting diagnostic challenge.